Tinjauan Yuridis Terhadap Penjatuhan Hukuman dalam Tindak Pidana Penjualan Obat-Obatan Tanpa Izin - Delieshia Marianti; Jopi Jopi; Gogo Lucky Hutagalung (DOKTRINA: JOURNAL OF LAW, 2020)
The aim of this research is to review the legal arrangements for drug traffickers without marketing authorization and the Judge's Consideration in imposing the law on perpetrators of Criminal Acts for Drug distribution without marketing authorization in Decision Number: 96 / Pid.SUS/2015/PN.Btl, research using normative juridical methods that are analytical descriptive in nature, Case Approach and Legislation: First, every business people who selling drugs and food in Indonesia must pocket a distribution permit in accordance with the provisions of the applicable laws and regulations in Indonesia, namely the Law Number 36 of 2009 concerning health reads "The availability of pharmaceuticals and medical devices can only be circulated after obtaining a marketing authorization" Law Number 30 of 2017 concerning the Food and Drug Supervisory Agency or abbreviated as POM as an institution in Indonesia which is tasked with overseeing the distribution of medicines and food in Indonesia. Second, the basic consideration of the judge to impose criminal sanctions against criminal offenses for the distribution of drugs without having a marketing authorization uses judicial judgment and non-judicial or sociological considerations with a single indictment, namely, violating Article 197 of Law Number 36 of 2009 concerning Health.